Steroids, steroid precursors, and neuroactive steroids in critically ill equine neonates. (July 2017) - Dembek, K.A.; Timko, K.J.; Johnson, L.M.; Hart, K.A.; Barr, B.S.; David, B.; Burns, T.A.; Toribio, R.E.
Highlights: In addition to cortisol, the secretion of multiple adrenocortical steroids is altered in critically ill foals. Progestogens and neuroactive steroids are increased in proportion to disease severity in hospitalised foals. Hospitalised foals with high progesterone concentrations are more likely to die than those with lower values. Dehydroepiandrosterone sulfate (DHEAS) is a good indicator of adrenal dysfunction in hospitalised foals. Abstract: Hypothalamic–pituitary–adrenal axis (HPAA) dysfunction has been associated with sepsis and mortality in foals. Most studies have focused on cortisol, while other steroids have not been investigated. The objectives of this study were to characterise the adrenal steroid and steroid precursor response to disease and to determine their association with the HPAA response to illness, disease severity, and mortality in hospitalised foals. All foals ( n  = 326) were classified by two scoring systems into three categories: based on the sepsis score (septic, sick non-septic [SNS] and healthy) and the foal survival score (Group 1: 3–18%; Group 2: 38–62%; Group 3: 82–97% likelihood of survival). Blood concentrations of adrenocorticotropic hormone (ACTH) and steroids were determined by immunoassays. ACTH–cortisol imbalance (ACI) was defined as a high ACTH/cortisol ratio. Septic foals had higher ACTH, cortisol, progesterone, 17α-OH-progesterone, pregnenolone, and androstenedione concentrations as well as higher ACTH/cortisol, ACTH/progesterone, ACTH/aldosterone, and ACTH/DHEAS ratios than SNS and healthy foals ( P <  0.01). Foals with DHEAS of 0.4–5.4 ng/mL were more likely to have ACI (OR = 2.5). Foals in Group 1 had higher ACTH, aldosterone, progesterone, and cortisol concentrations as well as ACTH/cortisol, ACTH/progesterone, and ACTH/DHEAS ratios than foals in Groups 2 and 3 ( P <  0.01). High progesterone concentrations were associated with non-survival and the cutoff value below which survival could be predicted was 23.5 ng/mL, with 75% sensitivity and 72% specificity. In addition to cortisol, the response to the stress of illness in foals is characterised by the release of multiple adrenal steroids. DHEAS and progesterone were good predictors of HPAA dysfunction and outcome in hospitalised foals.